Fungicide sensitivity levels in the Lithuanian Zymoseptoria tritici population in 2021 - Lavrukaitė, Karolina; Heick, Thies M.; Ramanauskienė, Jūratė; Armonienė, Rita; Ronis, Antanas (Frontiers in Plant Science, 2023)
Zymoseptoria tritici causes the disease known as septoria leaf blotch in winter wheat and is a major factor in yield loss worldwide. Farmers are inclined to use fungicides to protect their crops; however, the efficacy of these measures is rapidly decreasing due to the natural mechanisms of mutation emergence in pathogen populations. Increasing fungicide resistance is being recorded worldwide, therefore, screening of the current situation in Lithuania is essential to determine the subsequent steps of crop protection strategies. In this study, in vitro fungicide sensitivity tests, mutation detection, and field experiments were carried out. The mean EC50 values for prothioconazole-desthio and mefentrifluconazole were 0.14 and 0.28 mg/l, respectively. Increased frequency of the mutation S524T, linked to DMIs resistance, was observed. Results revealed that the dominant point mutation in the gene CYP51 was I381V, and the most frequent CYP51 haplotype was D13 (V136C, I381V, Y461H, S524T). The mutation G143A, linked to QoI resistance, was detected in ¾ of the population. Mutations conferring resistance to SDHIs were not detected in single pycnidium isolates. Two-year field experiments likewise showed no decline in field efficacy of SDHI fungicide in Lithuania. Moreover, the baseline sensitivity of the Lithuanian Z. tritici population to QiI fungicide fenpicoxamid was established. The findings of this study provide an update on the current status of fungicide resistance in the Lithuanian Z. tritici population.